Polyscias pinnata Balfour Aralia - Edward Gilman (EDIS)
This document provides an overview of the Balfour aralia (Polyscias pinnata), a shrub known for its variegated, glossy green leaves with white margins. It details the plant’s characteristics, including its height, spread, growth rate, and leaf arrangement. The document also covers its preferred growing conditions, such as light, soil, and water requirements, and highlights its uses in landscaping as a hedge, specimen, or container plant. Additionally, it addresses propagation methods and potential pest issues, noting that the plant is generally pest-resistant but can be affected by mites and scale. The Balfour aralia is praised for its ornamental features and versatility in various garden settings. Original publication date September 1999.